2022
DOI: 10.3390/molecules27175423
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Profiling and Antioxidant Property of Three Wild Edible Mushrooms from North East India

Abstract: The mushroom is an important food for the rural tribal populations in Manipur, because of its high nutritional contents. In this study, we report on the nutritional profile of three wild edible mushrooms consumed by the tribal populations of Manipur viz.: Macrocybe gigantea J124; Lactifluus leptomerus J201 and Ramaria thindii J470. The studied mushrooms possess a high protein content of 37.6%, 20.8% and 16.4%, respectively. They have a high vitamin C content with low vitamin B1, B2 and folic acid. Among the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 42 publications
0
13
1
Order By: Relevance
“…The synthetic antioxidant quercetin, on the other hand, had a 92.78% radical-scavenging activity, making M. gigantea a superior scavenger. The lyophilized methanolic extract of M. gigantea was previously discovered to possess a significant antioxidant activity of 75.73% at 200µg/mL (20) , but the current investigation demonstrated the maximum percentage of inhibition of 67.94% at 100µg/ml and lowest of 6.75% at 10µg/ml concentration.…”
Section: Scavenging Activity Of Dpph Radicalscontrasting
confidence: 62%
“…The synthetic antioxidant quercetin, on the other hand, had a 92.78% radical-scavenging activity, making M. gigantea a superior scavenger. The lyophilized methanolic extract of M. gigantea was previously discovered to possess a significant antioxidant activity of 75.73% at 200µg/mL (20) , but the current investigation demonstrated the maximum percentage of inhibition of 67.94% at 100µg/ml and lowest of 6.75% at 10µg/ml concentration.…”
Section: Scavenging Activity Of Dpph Radicalscontrasting
confidence: 62%
“…Mushrooms are an important source of beneficial dietary fiber for health 40 . The studied strains had varied content of fiber.…”
Section: Resultsmentioning
confidence: 99%
“…Carbohydrates is the largest nutritional component of mushrooms 40 . The results showed that all the wild strains had higher carbohydrate content than that of the control (36.61% of dry weight).…”
Section: Resultsmentioning
confidence: 99%
“…They obtained a coefficient of determination of 0.99 for the three fungi in the aqueous extracts, and the ethanolic extracts, it was 0.97 for Suillus granulatus, Coriolus versicolor, and Fuscoporia torulosa presented an R 2 of 0.81. In another work, Khumlianlal et al (2022) characterized three edible wild fungi of the tribal populations of Manipur. The percentage of inhibition of the DPPH radical was 73.1% for Macrocybe gigantea, 65.37% for Ramaria thindii, and 61.43% for Lactifluus leptomerus at a concentration of 1400 μg/mL.…”
Section: Antioxidant Activity Of Wild Edible Mushroomsmentioning
confidence: 99%